Anterior approaches to the cervicothoracic junction: a study on the surgical accessibility of three different corridors based on the CT images - Huang, Yi-xing; Ni, Wen-fei; Wang, Sheng; Xu, Hui; Wang, Xiang-yang; Xu, Hua-zi; Chi, Yong-long; He, Jia-wei (European spine journal, 2010)
To determine the location of left brachiocephalic vein (BCV) and tracheal bifurcation (TB) relative to the vertebral levels, and to ascertain the accessibility of three different corridors (C1: between the esophagus and trachea medially and the carotid sheath laterally, C2: between the right BCV and the brachiocephalic artery, and C3: between the ascending aorta and superior vena cava) for preoperative planning. From August 2008 to April 2009, normal chest CT scans of 150 subjects ranging in age from 18 to 78 years were selected. According to our definition, of the 150 studies, 132 T2 vertebral bodies (VBs) could be accessed through C1 (88.0%), 100 T3 VBs could be reached through C2 (66.7%), and 110 T4 VBs could be exposed through C3 (73.3%). The results suggest that the surgical accessibility of three different corridors is different and we conclude that T2, T3, and T4 are, respectively, readily accessible through C1, C2, and C3.